An exploration of the need for and cost of selected trade facilitation measures in Asia and the Pacific in the context of the WTO negotiations 2026-02-16T05:52:51+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (ESCAP studies in trade and investment ;, 2006)

(untitled)
"This publication presents the findings and results of an exploratory ARTNeT [Asia-Pacific Research and Training Network on Trade] study on the need for and cost of implementation of selected trade facilitation measures (TFMs) related to GATT Articles V, VIII and X. It is based on six ARTNeT working papers issued between January and April 2006"--Page vii